State-of-the-art review on electrolytes for sodium-ion batteries: Potential recent progress and technical challenges - Aslfattahia, Navid; Samylingam, L.; Maryam Sadat, Kiai; K., Kadirgama; Kulish, Vladimir; Schmirler, Michal; Said, Zafar (Elsevier Ltd, 2023)
Lithium batteries play a prominent role as a critical technology for advancing electric vehicles. However, establishing lithium-based technologies for mass storage encounters critical challenges such as materials availability and cost-efficiency. Hence, strategic approaches should be developed to address the existent challenges. Using sodium as new sustainable chemistry to replace lithium-based technologies tends to exhibit promising solution as the most appealing alternative. While exploring new electrode materials which has attracted significant interest from eminent researchers for sodium-ion batteries, research activities related to electrolyte are less attention paid. This paper reviews the most recent articles on developing and improving the electrolytes for sodium-ion batteries, particularly liquid electrolytes. This is the latest comprehensive discussion related to sodium-ion batteries with different type of electrolytes and a particular focus on the advantages/disadvantages in order to improve efficiency of these novel technologies as well as comprehensive discussion on the application of advanced nanomaterials towards these devices.